2013
DOI: 10.7150/jca.6638
|View full text |Cite
|
Sign up to set email alerts
|

TGF-β2: A Novel Target of CD44-Promoted Breast Cancer Invasion

Abstract: We have developed a tetracycline (tet)-off regulated expression of CD44s gene in the breast cancer (BC) cell line MCF-7 (B5 clone) and identified TGF-β2 (Transforming Growth Factor beta-2; 3 fold induction) as a potential CD44-downstream transcriptional target by microarray analysis. To further validate this finding, the same RNA samples, used for microarray analysis and their corresponding protein lysates, collected from the BC cell line MCF-7-B5, were examined for CD44 expression in the presence of HA. Our r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
40
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(45 citation statements)
references
References 34 publications
2
40
0
Order By: Relevance
“…Notably, TGF‐β is a factor key to the preserving of the mesenchymal‐like phenotype in circulating cancer cells, due to CD44S isoform downstream signaling, which regulates vimentin and Smad2 levels (Mima et al, ) and as discussed by Heldin et al (). Furthermore, Ouhtit et al () suggest that HA/CD44s signaling, which initiates ATF/CREB activity, might facilitate TGF‐β2 transcription.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, TGF‐β is a factor key to the preserving of the mesenchymal‐like phenotype in circulating cancer cells, due to CD44S isoform downstream signaling, which regulates vimentin and Smad2 levels (Mima et al, ) and as discussed by Heldin et al (). Furthermore, Ouhtit et al () suggest that HA/CD44s signaling, which initiates ATF/CREB activity, might facilitate TGF‐β2 transcription.…”
Section: Discussionmentioning
confidence: 99%
“…Three sub-types of TGF-β are found in this family, including TGF-β1, TGF-β2 and TGF-β3. In reference to cancer, all the three isoforms of TGF-β are involved in cancer progression (22)(23)(24). For colon cancer, the dysfunction or loss of TGF-β signaling will promote progression of cancer (25,26).…”
Section: Tgf-β1/pten/pi3k Signaling Plays a Critical Role In The Antimentioning
confidence: 99%
“…As shown in Table 8.1, basal-like cells that are highly metastatic exhibit high expression of CD44s. It has been demonstrated that although TGFβ signaling is the major regulator of EMT and maintains the stem cell phenotype (Scheel et al, 2011), CD44s, but not the variant isoforms, plays an important role in TGFβ-mediated mesenchymal phenotype associated with vimentin expression and high levels of Smad2 in nuclei (Mima et al, 2012;Ouhtit et al, 2013). Nevertheless, recent studies in our laboratory revealed that signals triggered via the binding of HAS2synthesized HA on bone-metastasizing breast cancer cells, to CD44 expressed by microvascular endothelial cells, promotes the adhesiveness between breast cancer cells and endothelial cells and thus cancer cell intravasation (Olofsson, Porsch, & Heldin, 2014).…”
Section: Ha-cd44 Interactions: a Regulatory Network During Tgfβ-mediamentioning
confidence: 99%